2023
DOI: 10.1002/dmrr.3598
|View full text |Cite
|
Sign up to set email alerts
|

Changes in early optical coherence tomography angiography among children and adolescents with type 1 diabetes: Relation to fibroblast growth factor 21

Abstract: Aims Current diagnostic and treatment modalities target late stages of diabetic retinopathy (DR) when retinopathy has already been established. Novel and more sensitive strategies are needed. Optical coherence tomography angiography (OCTA) permits non‐invasive visualisation of retinal microcirculation. Fibroblast growth factor‐21 (FGF21) plays an important role in glucose and lipid homoeostasis. This study assesses early OCTA changes among children and adolescents with type 1 diabetes (T1DM) compared to fundus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
0
1
0
Order By: Relevance
“…Our findings were in concordance with previous research by Czakó et al ( 18 ), who found that DM duration was strongly associated with decreased retinal VD after interaction analysis with the effects of systemic risk factors, and by Qian et al ( 11 ), who reported a negative correlation between DM duration and OCTA metrics such as SCP-VD and SCP-PD in 1118 DM patients. Furthermore, larger FAZ and lower retinal capillary densities in children and adolescents with diabetes were observed in a case–control study ( 19 ), and these changes are associated with DM duration and poor glycemic control.…”
Section: Discussionmentioning
confidence: 97%
“…Our findings were in concordance with previous research by Czakó et al ( 18 ), who found that DM duration was strongly associated with decreased retinal VD after interaction analysis with the effects of systemic risk factors, and by Qian et al ( 11 ), who reported a negative correlation between DM duration and OCTA metrics such as SCP-VD and SCP-PD in 1118 DM patients. Furthermore, larger FAZ and lower retinal capillary densities in children and adolescents with diabetes were observed in a case–control study ( 19 ), and these changes are associated with DM duration and poor glycemic control.…”
Section: Discussionmentioning
confidence: 97%
“…In a recent study where optical coherence tomography angiography (OCTA) was used, higher levels of FGF21 were found in children and adolescents with type 1 diabetes ( n = 100) compared to the same number of age, gender, and Tanner-matched healthy controls ( n = 100). FGF21 was also higher among patients with type 1 diabetes and OCTA changes compared to those without [ 28 ]. We could not in our study however, observe any difference in FGF21 levels with regard to diabetes duration.…”
Section: Discussionmentioning
confidence: 99%